The Role of Notaries and Land Titles Registrar in Collecting Duties on The Land and Building Rights Acquisition on The Making of Sale and Purchase Deeds in Singaraja City - Nyoman Edy Febriana; I Wayan Parsa; I Gede Artha; I Nyoman Bagiastra (Jurnal Akta, 2022)
The main objective of this study is to know the role of Land Titles Registrar (PPAT) in collecting duties on the Land and Building Rights Acquisition (BPHTB) on the sale and purchase transactions in Singaraja City. Furthermore, we investigate the duties and obligations of the PPAT in supervising the payment of BPHTB. The research was conducted using a qualitative approach with empirical juridical methods. The main finding is the role of PPAT as the official who makes BPHTB quotations during sales and purchase transactions in Singaraja City shows a very important role. Also, we have presented the duty and obligation of PPAT in supervising the payment of BPHTB is to make taxpayers aware that taxes are paid in accordance with applicable regulations.